Reconstruction of MUI Fatwa No. 7 of 2000 on the Dispatch of Female Migrant Workers: A Psychological Perspective - Izzatur Rusuli (Yinyang: Jurnal Studi Islam Gender dan Anak, 2024)
Women working abroad have become a significant phenomenon in Indonesia, prompting the Indonesian Ulema Council (MUI) to issue a fatwa that regulates and provides guidance for those pursuing it. This study aims to analyze the positive and negative psychological impacts of women working abroad and propose solutions to address these challenges. Additionally, this study also analyzes the MUI fatwa regarding delivering female workers abroad. This article is a literature review using content analysis as a data analysis method. The results of this paper show that psychologically women who work abroad have a positive impact such as supporting their family's economic needs and contributing to the national economy. Meanwhile, the negative impacts include higher rates of divorce, mental health issues, neglect of childcare responsibilities, and the development of consumerist behavior and poor financial management. The way to overcome these negative impacts include establishing joint commitments, choosing legal and authorized agents, setting specific time targets for employment, and maintaining regular communication with family members. Therefore, the MUI fatwa regarding this matter is relevant, it is suggested that a clause on joint commitments, particularly for married women, be included to enhance its effectiveness.